A Novel Framework To Investigate The Impact Of Social Media Advertising Features On Customer Purchase Intention Using Bwo-Dann - Meena Zenith N (IAES Indonesian Section, 2022)
Social Media (SM) has turned out to be a platform for marketing as well as advertising activities. In relation to SM Advertising (SMA), the cultural influence on consumers’ behavior as well as attitude is more vital. Organizations have used up loads of money, time, and also resources on SMA. Nevertheless, it is always a challenge for the organizations to model SM advertisement in a means to effectively attract and also motivate customers into purchasing their brands. This paper proposed a novel framework to scrutinize the SMA features’ impact on Customer Purchase Intention (CPI) by means of the BWO-DANN. Initially, the questionnaires are given to the various customer and their answers are collected. Then, answers will be uploaded and are converted into numerical format into the system. Next, the CSGA-KM is utilizedfor clustering the questionnaires on the base of personal information. Then the BWO-DANN is utilized to train the converted questionnaire set. After that, the system is tested by utilizing KFCV. Finally, through the mean model, CPI is founded out. The extensive experimentation’s outcomes illustrated that the system trounced the other methodologies, and also it is best to examine the CPI.